Citations and Convictions: One Community’s Coordinated Response to Intimate Partner Violence & Efforts toward Offender Accountability - Beldin, Kerry (2015)
In 1996, a coordinated community response (CCR) was formally established in a mid-sized Midwestern city to improve the criminal justice response to intimate partner violence (IPV). Data for this study included all IPV-related incidents to which the local police department responded since the establishment of the CCR for a fourteen year period. Effective CCRs provide for IPV offender accountability through citation and prosecution of IPV-related crimes. Concerns about demographic variables affecting citation and prosecution rates have been identified in the literature. Compared to national statistics, gender differences were consistent but higher citation and conviction rates were identified in this community. While differences related to race were found, they were small in size. Although lack of data available from the time prior to the implementation of the CCR model for comparison precludes a definitive conclusion about the effectiveness of the CCR, our findings suggest there is benefit to having one